Career Decision Making Self-Efficacy: Confidence of Indonesian Professional Psychology Masters Students in Making Career Decisions - Lasmini, Hesti Muthia; Abidin, Zainal (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This study aims to describe Career Decision Making Self-Efficacy (CDMSE) among master's students in professional psychology programs in Indonesia. The background of this study lies in the various challenges faced by master's students in professional psychology programs as prospective psychologists, such as limited job opportunities, low public awareness of mental health, and study periods that could exceed 4 semesters for this research. Data was collected by using semi-structured interviews technique through case study. Data analysis utilized a thematic analysis based on Crites's five career selection competencies to determine the domains of Career Decision-Making Self-Efficacy from Taylor & Betz (1983), namely accurate self-appraisal, gathering occupational information, goal selection, making plans, and problem-solving. Credibility in this study was established through triangulation and enhancing persistence. The results of this study indicate that the participants possess self-efficacy in accurately describing their capabilities related to their chosen career or major (accurate self-appraisal). However, the process of searching for job information and field of work choosing remains incomplete and superficial (gathering occupational information). This could potentially hinder their confidence in setting career goals (goal selection), making future career plans (making plans), and overcoming obstacles that may impede career decision-making (problem-solving).Penelitian ini bertujuan untuk mengetahui gambaran tentang Career Decision Making Self-Efficacy (CDMSE) dari mahasiswa magister Psikologi profesi di Perguruan Tinggi di Indonesia. Penelitian ini dilatarbelakangi oleh adanya berbagai tantangan yang dihadapi oleh mahasiswa magister Psikologi profesi sebagai calon Psikolog, seperti peluang pekerjaan yang kurang memadai, rendahnya kesadaran masyarakat terhadap kesehatan mental, dan lama studi yang dapat mencapai lebih dari 4 semester. Metode yang digunakan adalah studi kasus dengan teknik pengumpulan data melalui wawancara semi-terstruktur. Pengolahan data menggunakan analisis tematik yang mengacu pada 5 (lima) Kompetensi Pilihan Karier Crites yang digunakan untuk menentukan domain pada Career Decision Making Self-Efficacy dari Taylor & Betz (1983), yakni accurate self-appraisal, gathering occupational information, goal selection, making plans, dan problem solving. Kredibilitas dalam penelitian ini dilakukan dengan triangulasi dan meningkatkan ketekunan. Hasil dari penelitian ini adalah bahwa para partisipan sudah memiliki efikasi diri dalam menggambarkan kemampuan diri secara tepat atau akurat terkait dengan karier atau jurusan yang dipilih (accurate self-appraisal). Akan tetapi proses pencarian informasi pekerjaan dan bidang pekerjaan yang akan dipilih masih belum lengkap dan mendalam (gathering occupational information). Hal tersebut diprediksi dapat menghambat mereka untuk memiliki keyakinan bahwa mereka mampu menetapkan tujuan karier (goal selection), membuat perencanaan karier di masa depan (making plans), serta mengatasi masalah terkait hal-hal yang dapat menghambat pengambilan keputusan karier (problem solving).